1989
DOI: 10.1152/jappl.1989.67.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-adrenoceptor blockade on renin-aldosterone and alpha-ANF during exercise at altitude

Abstract: The renin-aldosterone system may be depressed in subjects exercising at high altitude, thereby preventing excessive angiotensin I (ANG I) and aldosterone levels, which could favor the onset of acute mountain sickness. The role of beta-adrenoceptors in hormonal responses to hypoxia was investigated in 12 subjects treated with a nonselective beta-blocker, pindolol. The subjects performed a standardized maximal bicycle ergometer exercise with (P) and without (C) acute pindolol treatment (15 mg/day) at sea level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Therefore, one may suggest that the decrease in Hct in hypoxic rats treated by acetazolamide was not fully explained by the decrease in erythropoiesis (as suggested by the decrease in percentage of reticulocytes), and was also probably the resulting effect of the plasma volume rise, which could be interpreted as a physiological adaptation for maintaining blood volume at the normal value. The hypoxia-induced decrease in plasma volume was probably attributed to the well-known blunting effect of hypoxia on the renin-aldosterone system [21] and other complex mechanisms, such as peripheral arterial chemoreception [23,24]. The mechanism by which acetazolamide could oppose this blunting effect remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one may suggest that the decrease in Hct in hypoxic rats treated by acetazolamide was not fully explained by the decrease in erythropoiesis (as suggested by the decrease in percentage of reticulocytes), and was also probably the resulting effect of the plasma volume rise, which could be interpreted as a physiological adaptation for maintaining blood volume at the normal value. The hypoxia-induced decrease in plasma volume was probably attributed to the well-known blunting effect of hypoxia on the renin-aldosterone system [21] and other complex mechanisms, such as peripheral arterial chemoreception [23,24]. The mechanism by which acetazolamide could oppose this blunting effect remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise at HA still produces a rise in PRA and PAC (Maher et al, 1975, Milledge et al, 1983a, Lawrence et al, 1991, Rock et al, 1993, though not all studies confirm this (Zaccaria et al, 1998). The rise in PAC with exercise at HA is of smaller magnitude than at SL (Bouissou et al, 1989 andBartsch et al, 1991), and has been found to be more subdued with acute, rather than chronic (14-16 days), exposure (Rock et al, 1993).…”
Section: Woods and Montgomerymentioning
confidence: 99%
“…Two events occurring during RSL may initiate PV recovery through water retention: (1) high-altitude hypovolemia, which induced appropriate hormonal changes, and (2) acute reoxygenation, i.e., suppression of hypoxia, known to be a potent stimulator of atrial natriuretic factor (ANF) secretion and an inhibitor of aldosterone release [2,20]. The present study describes PV recovery upon early RSL after high-altitude exposure with concomitant changes in major fluid-regulating hormones and water intake/output.…”
Section: Introductionmentioning
confidence: 99%